(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Scar ectopic pregnancy is the rarest form of ectopic pregnancy and has been increasingly diagnosed all over the world. Usually when a blastocyst implants on the fibrous tissue of the previous Caesarean scar is called scar ectopic. This type of abnormal implantation of embryo can occur following hysterotomy, dilatation and curettage ,abnormal placentation surgery on uterus like myomectomy ,hysteroscopy and manual removal of placenta. The incidence is increased due to increase in number of Caesarean deliveries. Trans vaginal Sonography helps in early diagnosis. Early diagnosis leads to prompt management and improves the outcome by allowing preservation of future fertility. Excision of trophoblastic tissues using laparotomy or laparoscopy, systemically administered methotrexate, and more recently uterine artery embolization are the treatment options for scar ectopic. When TVS is inconclusive, MRI can be recommended. We are reporting here a case of first trimester caesarean scar pregnancy with viable fetus in the process of rupture, where uterine repair could be done to preserve the future fertility. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 154-156